SIRT1, a novel transcriptional downstream target of CD44, linking its deacetylase activity to tumor cell invasion/metastasis - Ahmad, Salma M. S.; Al-Mansoob, Maryam; Ouhtit, Allal (Frontiers in Oncology, 2022)
Our tetracycline-off-inducible CD44 expression system previously established in mouse model, revealed that activation of CD44 with its major ligand hyaluronan (HA) promoted breast cancer (BC) metastasis to the liver. To identify the mechanisms that underpin CD44-promoted BC cell invasion, microarray gene expression profiling using RNA samples from (Tet)-Off-regulated expression system of CD44s in MCF7 cells, revealed a set of upregulated genes including, nuclear sirtuin-1 (SIRT1 also known as NAD-dependent deacetylase), an enzyme that requires NAD+ as a cofactor to deacetylate several histones and transcription factors. It stimulates various oncogenic pathways promoting tumorigenesis. This data suggests that SIRT1 is a potential novel transcriptional target of CD44-downstream signaling that promote BC cell invasion/metastasis. This review will discuss the evidence supporting this hypothesis as well as the mechanisms linking SIRT1 to cell proliferation and invasion.